Hubungan Persepsi Pengguna Busy Book Terhadap Stimulasi Perkembangan Kognitif Berpikir Simbolik Anak usia 5-6 Tahun - Elrika Rosa Aisyah; Sri Widayati; Mallevi Agustin Ningrum; Kartika Rinakit Adhe (LP. Ma'arif Janggan Magetan, 2024)
It is necessary to stimulate the cognitive development of symbolic thinking in children, so that the development of symbolic thinking in children can develop well. Stimulation can be done using various types of media, one of which is busy books. Busy book media is learning media made from flannel and contains various activities that can develop aspects of children's development. The perception of busy book users is carried out to increase insight and innovation for other users so that they don't just use monotonous media. This research aims to determine the relationship between busy book users' perceptions of stimulating the cognitive development of symbolic thinking in children aged 5-6 years. The number of samples used in this research was 88 people. The research location was carried out in the West Surabaya area. This research uses a quantitative correlation approach. The collection technique used is a questionnaire and uses data analysis techniques with product moment correlation tests and simple linear regression analysis. The results of this test were carried out using SPSS version 25 for Windows. The results of the research that has been carried out show that the perception of busy book users regarding the stimulation of cognitive development of symbolic thinking is 0.775, which is classified as quite high. Based on the results of this research, it can be concluded that there is a relationship between busy book users' perceptions of stimulating the cognitive development of symbolic thinking in children aged 5-6 years.